Clinicopathological Characteristics of Gastritis Associated with Helicobacter pylori: A Two-Year Retrospective Analysis - Zaet, Abdurraouf; Mohamed Alghoj; Ibrahim Eswaey; Nuri Ahwij; Hanan Alwuheeshi; Altayeb Elazomi (AlQalam Journal of Medical and Applied Sciences, 2026)
Helicobacter pylori infection continues to represent one of the most prevalent chronic bacterial infections on a global scale and constitutes a principal etiological factor for gastritis, peptic ulcer disease, and gastric malignancies. The present investigation sought to delineate the clinicopathological attributes of H. pylori-related gastritis among individuals subjected to endoscopic assessment. A retrospective review was performed on 82 histologically verified cases of H. pylori infection identified from gastric mucosal biopsies collected over a 24-month interval (2023-2024) at private healthcare facilities situated in the western region of Libya. Variables including demographic parameters, clinical manifestations, endoscopic observations, and histopathological severity were evaluated employing standardized histopathological criteria. The investigation encompassed 82 participants with a mean chronological age of 39.3 ± 18.0 years (spanning 13-77 years). Female subjects constituted the majority (62.2% versus 37.8%). The preponderance of cases (78.0%) exhibited active chronic gastritis, with moderate severity representing the most frequent finding (46.3%), followed by severe (29.3%) and mild (13.4%) presentations. Epigastric discomfort emerged as the principal presenting manifestation (63.4%). Concomitant pathological discoveries encompassed duodenitis (12.2%), ulcerative or erosive lesions (6.1%), and intestinal metaplasia (3.7%). These findings indicate a substantial prevalence of active H. pylori infection across diverse age demographics, with a marked female preponderance. The considerable proportion of moderate to severe active gastritis emphasizes the necessity of timely diagnostic evaluation and eradication therapy to avert progression toward more severe sequelae, including gastric carcinoma.